The Potential Use of Antibiotics Against Helicobacter pylori Infection: Biopharmaceutical Implications - Miri, Amir Hossein; Kamankesh, Mojtaba; Llopis-Lorente, Antoni; Liu, Chenguang; Wacker, Matthias G.; Haririan, Ismaeil; Asadzadeh Aghdaei, Hamid; Hamblin, Michael R.; Yadegar, Abbas; Rad-Malekshahi, Mazda; Zali, Mohammad Reza (Frontiers in Pharmacology, 2022)
Graphical Abstract